2021
DOI: 10.1038/s41398-021-01356-0
|View full text |Cite
|
Sign up to set email alerts
|

The brain at war: effects of stress on brain structure in soldiers deployed to a war zone

Abstract: In search of the neural basis of severe trauma exposure and post-traumatic stress disorder (PTSD), a multitude of cross-sectional studies have been conducted, most of them pointing at structural deficits in the hippocampus and medial prefrontal cortex including the anterior cingulate cortex (ACC) and ventromedial prefrontal cortex (vmPFC). Since cross-sectional studies are silent to causality, the core question remains: which brain structural alterations constitute a risk factor for disease and therewith prece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…In a broader perspective, previous research has suggested that the events that happen in the society have a clear impact on the brain. For example, previous studies have identified reductions in the prefrontal cortex following earthquakes 11 and warzone experiences 12 . One study has demonstrated how a single extreme aversive global event may impact fear circuits by linking individuals’ geographical proximity to the site of 9/11 terrorist attacks to the reactivation of the amygdala during memory recollection 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In a broader perspective, previous research has suggested that the events that happen in the society have a clear impact on the brain. For example, previous studies have identified reductions in the prefrontal cortex following earthquakes 11 and warzone experiences 12 . One study has demonstrated how a single extreme aversive global event may impact fear circuits by linking individuals’ geographical proximity to the site of 9/11 terrorist attacks to the reactivation of the amygdala during memory recollection 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is not clear whether the resilience cluster represents general resilience against stressors (a genetic predisposition), so that the same characteristics may protect individuals from other mental health disorders, such as depressive ones (Bromis et al, 2018), or specific protective qualities against traumatic events. Third, although some studies sought to demonstrate causality (Gilbertson et al, 2002;Kasai et al, 2008;Kremen et al, 2012;Kühn et al, 2021), in the present study it is not possible to determine whether the volumetric differences between the clusters preceded the trauma exposure or were acquired as the result of confronting trauma without developing PTSD. The differences between the clusters in race may reflect the way in which social determinants of mental health may shape health inequalities, for example by causing added risk, then leading to lower resilience (Alegría et al, 2018;Bailey, 2015).…”
Section: Sensitivity Analysesmentioning
confidence: 83%
“…Reduced thalamic volume is reportedly associated with the frequency and duration of re-experience of trauma in traumatized humans ( 39 ). Thalamic volume is also reportedly associated with childhood maltreatment among high school students and exposure to trauma among deployed soldiers ( 15 , 40 ). While reduced thalamic volume is reportedly associated with psychological disturbances after trauma, increased thalamic GM volume might reflect neurobiological resilience to trauma.…”
Section: Discussionmentioning
confidence: 99%